2009
DOI: 10.2478/s11535-009-0041-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of antioxidant capacity and phenolic compounds of berries, chokecherry and seabuckthorn

Abstract: Antioxidant capacity and phenolic compounds (phenolic acids and anthocyanins) of four berry fruits (strawberry, Saskatoon berry, raspberry and wild blueberry), chokecherry and seabuckthorn were compared in the present study. Total phenolic content and total anthocyanin content ranged from 22.83 to 131.88 g/kg and 3.51 to 13.13 g/kg, respectively. 2,2-Diphenyl-1-picryhydrazyl free radical scavenging activity ranged from 29.97 to 78.86%. Chokecherry had the highest antioxidant capacity when compared with berry f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
64
2
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 47 publications
9
64
2
4
Order By: Relevance
“…The increase in antioxidant activity may be explained by the increase of solvent polarity. These results have been confirmed by other studies using the FRAP (Ardestani and Yazdanparast, 2007;Atmani, 2009;Li et al, 2009) and DPPH (Tian et al, 2009;Fabri et al, 2009) assays. Antioxidant and radical scavenging properties of plant extracts is associated with the presence of phenolic compounds which are able to donate hydrogen to the radical.…”
Section: Total Antioxidant Capacity (Tac)supporting
confidence: 85%
“…The increase in antioxidant activity may be explained by the increase of solvent polarity. These results have been confirmed by other studies using the FRAP (Ardestani and Yazdanparast, 2007;Atmani, 2009;Li et al, 2009) and DPPH (Tian et al, 2009;Fabri et al, 2009) assays. Antioxidant and radical scavenging properties of plant extracts is associated with the presence of phenolic compounds which are able to donate hydrogen to the radical.…”
Section: Total Antioxidant Capacity (Tac)supporting
confidence: 85%
“…The samples showed very strong scavenging activity against DPPH after 30minutes with the organic freeze dried blueberry displaying 49%, while the organic 'Draper' and 'Duke' variety ranged between 43% and 28% respectively. The data collected are in agreement with previous studies which showed results in different varieties of blueberries ranging between 28% -60% [30]. This proved that blueberries are a good source of antioxidants which are used in eliminating and protecting cells against oxidative stress and fighting free radicals.…”
Section: Resultssupporting
confidence: 91%
“…1ml of the blueberry sample was reduced by a factor of 25 with distilled water and titrated by 0.05mg/ml DCPIP reagent to get a titre of 0.3ml and 0.4ml (Table 3) [16,[28][29][30].…”
Section: Resultsmentioning
confidence: 99%
“…2) the test for antioxidant activity for the capture of organic free radical 2,2-diphenyl-1-picryl-hydrazyl (DPPH) consisted of mixing 100 µL of the extracted solution with 1.9 mL of the DPPH solution. Subsequent readings took place in the spectrophotometer at 515 nm for 1 h to allow the absorbance to stabilize (LI et al, 2009). …”
Section: Methodsmentioning
confidence: 99%